PreSMA stimulation changes task‐free functional connectivity in the fronto‐basal‐ganglia that correlates with response inhibition efficiency. Issue 9 (4th May 2016) - Xu, Benjamin; Sandrini, Marco; Wang, Wen‐Tung; Smith, Jason F.; Sarlls, Joelle E.; Awosika, Oluwole; Butman, John A.; Horwitz, Barry; Cohen, Leonardo G.
Abstract: Previous work using transcranial magnetic stimulation (TMS) demonstrated that the right presupplementary motor area (preSMA), a node in the fronto‐basal‐ganglia network, is critical for response inhibition. However, TMS influences interconnected regions, raising the possibility of a link between the preSMA activity and the functional connectivity within the network. To understand this relationship, we applied single‐pulse TMS to the right preSMA during functional magnetic resonance imaging when the subjects were at rest to examine changes in neural activity and functional connectivity within the network in relation to the efficiency of response inhibition evaluated with a stop‐signal task. The results showed that preSMA‐TMS increased activation in the right inferior‐frontal cortex (rIFC) and basal ganglia and modulated their task‐free functional connectivity. Both the TMS‐induced changes in the basal‐ganglia activation and the functional connectivity between rIFC and left striatum, and of the overall network correlated with the efficiency of response inhibition and with the white‐matter microstructure along the preSMA–rIFC pathway. These results suggest that the task‐free functional and structural connectivity between the rIFCop and basal ganglia are critical to the efficiency of response inhibition. Hum Brain Mapp 37:3236–3249, 2016 . ©2016 Wiley Periodicals, Inc.